Geodetic monitoring of deformations of the earth's surface and the main gas pipeline in the area affected by mining operations - N. Kolesnik; M. Kozhemiako (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ)
Abstract. The importance of the task of calculating and analyzing the displacements and deformations of the earth's surface for monitoring the state of objects located on the earth's surface within the influence of mining operations is substantiated. Studies have been conducted that indicate that the actual values of earth surface displacements and deformations differ significantly from the calculated values determined by standard methods. Today, when developing measures to protect objects on the earth's surface, a regulatory methodology is used that applies an overload coefficient. However, it does not make it possible to determine the actual range of the variation of subsidence and deformation of the earth's surface.